STUDENTS’ PERCEPTION OF USING PADLET IN LEARNING ENGLISH - Setiawati Setiawati (AL-ISHLAH: Jurnal Pendidikan, 2020)
This study aimed to know students’ perception of using Padlet in learning English in the first semester of Islamic Education Department STAI Hubbulwathan Duri. This research used a quantitative approach. The design of the research was a survey. In this research, the writer conducted a descriptive survey. The total population was the first semester of Islamic education STAI Hubbulwathan Duri. The undergraduate students have the same qualification and academic background before doing a survey. They had ever learned English by using Padlet. The sample of this research was 61 respondents. The total rating percentage of students’ perception using Padlet in learning English 54.5%. it was the agreed category. This category showed the respondents Agree to use Padlet application in the teaching-learning process. Based on the overall mean is 3.15 and the standard deviation is 0.673 respondents agree used it in the teaching-learning process. The respondents gave positive responses. It meant that the Padlet platform gave a positive perception to use it in the English learning process.